Glyphosate Exposure, Oxidative Stress, Mitochondrial Dysfunction, and Mortality Risk in US Adults: Insights from the National Health and Nutrition Examination Survey - Yu-Wei Fang; Hsuan-Cheng Lin; Chikang Wang; Chien-Yu Lin (Toxics)
Purpose: Glyphosate and glyphosate-based herbicides (GBHs) are widely used across the globe. Experimental research indicates that these herbicides may elevate oxidative stress and impair mitochondrial function. However, the relationship between glyphosate exposure, oxidative stress, and mitochondrial function remains poorly characterized in epidemiological studies. In particular, the role of oxidative stress and mitochondrial function biomarkers in mediating the mortality risk associated with glyphosate exposure in nationally representative populations is not well understood. Approach and Results: In this study, we utilized data from the 2013–2014 National Health and Nutrition Examination Survey (NHANES), encompassing 1464 participants aged 18 years and older. This dataset was linked to mortality records from the National Center for Health Statistics (NCHS), with follow-up data extending through 2019. The primary objective was to examine the associations between urinary glyphosate levels and biomarkers of oxidative stress and mitochondrial function—specifically pyrazino-s-triazine derivative of 4-α-hydroxy-5-methyl-tetrahydrofolate (MeFox) and methylmalonic acid (MMA)—and to evaluate the role of these biomarkers in influencing glyphosate-related mortality outcomes. Results: Urinary glyphosate levels were positively associated with serum MMA and MeFox in weighted multiple linear regression models. For MMA, glyphosate showed significant positive associations in both adjusted models (Model 2: β = 0.061, p = 0.001). Similarly, urinary glyphosate was strongly associated with MeFox in all models (Model 2: β = 0.215, p < 0.001). During a median follow-up of 69.57 months, 116 deaths occurred, including 44 from cardiovascular causes. Glyphosate was not significantly associated with all-cause or cardiovascular mortality in the overall population. However, subgroup analysis revealed significant associations in individuals with higher MeFox levels (≥50th percentile) for all-cause mortality (HR = 1.395, p = 0.027) and borderline associations for cardiovascular mortality (HR = 1.367, p = 0.051). When adjusted for MMA, glyphosate was significantly associated with increased all-cause mortality in participants with MMA levels below the 50th percentile (HR = 2.679, p = 0.001), with a significant interaction between glyphosate and MMA for all-cause (p = 0.002) and cardiovascular mortality (p = 0.038). Conclusions: In this comprehensive analysis of NHANES data, urinary glyphosate levels were associated with biomarkers of oxidative stress and mitochondrial function. While no overall mortality associations were observed, glyphosate exposure was linked to increased all-cause mortality in subgroups with lower MMA or higher MeFox levels. These findings highlight the role of oxidative stress and mitochondrial function in glyphosate-related health risks and the need for further research to identify vulnerable populations.